A Curriculum of Ideology: Use and Abuse of Modern History Education in Russia and the United States - Tsyrlina-Spady, Tatyana; Lovorn, Michael (International Dialogues on Education Journal, 2015)
This paper examines the extents to which students in high school history classes in Russia and the United States are subjected to curricula, texts, images, and symbols that promote patriotic and nationalistic ideology. The authors performed a comparative content analysis of various commonly used Russian and American 20th century history textbooks. This analysis included an exploration of textual attention to ideological agendas, including the heroification of certain political and military figures, and led researchers to a series of implications regarding the impact of this manipulation of content on students’ general understandings of history, their country’s place in history, as well as an overall effect on their personality and character development. Most notably, analysis of recent textbooks in both countries revealed clear agendas intended to foster and promote national identity and patriotism.